Financial Improvement Strategy of PT. Wahana Interfood Nusantara Tbk. Using The Cash Waterfall Method - Muhammad Hanivan Titunanda; Oktofa Yudha Sudrajad; Erman Arif Sumirat (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This paper examines the financial issues of PT. Wahana Interfood Nusantara Tbk., a manufacturer of cocoa and chocolate goods, and recommends improvements through the Cash Waterfall Method and the \ optimization of their capital structure. As of the third quarter of 2024, the company had a Debt to Equity Ratio of 261% and a negative Interest Coverage Ratio of -0.66, indicating significant financial distress due to excessive debt servicing. This research utilized financial modeling tools such as CAGR forecasting, linear regression, and ARIMA methods, revealing significant shortcomings in cash flow management and recommending a negotiation to debitors of one-year grace period to mitigate severe urgent financial pressures. The Cash Waterfall Method is applied to enhance debt servicing, business viability, and reinvestment, although its application is tempered by its capacity to improve liquidity and recover the company's financial health. The analysis indicates that the unutilized capacity of the newly constructed Sumedang factory, which has an annual production capacity of 20,000 tons, combined with the existing yearly production objective of 6,000 tonnes, is likely to improve the company's overall growth potential. This properly strategized investment necessitates assertive marketing and distribution tactics to facilitate the company's enhancement of net income while concurrently diminishing its need on external financing sources. The study concludes that while the optimal capital structure remains unattainable under current financial distress, a restructured approach focusing on operational recovery and disciplined cash flow management is imperative. Recommendations include leveraging increased production capacity, implementing strategic marketing initiatives, and pursuing shareholder returns once financial stability is restored. This research contributes to understanding the interplay between capital structure, cash flow prioritization, and operational performance in heavily indebted firms, offering actionable insights for practitioners and policymakers in similar contexts.